Susceptibility to risky sexual behaviours in the polish population aged 15-63 - Wojciechowski, Piotr; Żurek, Katarzyna; Wujec, Zuzanna; Nawrocki, Maciej (Journal of Education, Health and Sport, 2022)
Frequent involvement in risky sexual behaviors among members of society is a threat to their health. It’s also a social problem, as it increases the risk of spreading STDs and unwanted pregnancies. The aim of the study was to check the susceptibility to risky sexual behaviors in the Polish population aged 15-63. The research method was an original online questionnaire. A total of 294 responses were obtained from people of different gender, age, place of residence and level of education. The results were then statistically analyzed. 84% of respondents had undergone sexual initiation. The remaining respondents were excluded from further study. The average age of initiation was 18.2 years. 73% of respondents claim to never use condoms during oral sex. 22% of respondents use other methods instead of condoms. In the past 12 months, 21% of respondents had more than 1 sexual partner and 36% often had sex after drinking alcohol. 60% of respondents have never tested for STDs, and only 5% do it regularly when changing sexual partners. Subjects of concern are: large proportion of respondents who do not protect themselves during oral sex, a small number of respondents who regularly get tested for STDs, and a significant group of people who declare that they frequently have sex under the influence of alkohol.